Endovascular Management of Infected Iliofemoral Pseudoaneurysms: A Case Series. (August 2016) - Moulakakis, Konstantinos G.; Sfyroeras, George S.; Alexiou, Vangelis G.; Kakisis, John; Lazaris, Andreas; Vasdekis, Spyridon N.; Brountzos, Elias N.; Geroulakos, George
The treatment of infected iliofemoral pseudoaneurysms is challenging and controversial. We present our experience regarding the efficacy and outcome of endovascular treatment of infected iliofemoral arterial pseudoaneurysms with covered stents. Our experience with 5 cases showed that stent grafting combined with antibiotic therapy and provisional drainage may be a safe and effective option in patients with cancer, patients with history of multiple hip revisions, and drug-addicted users. In our small case series, the reinfection rate was null and no covered stent thrombosis occurred. These results are fairly encouraging, but further studies with longer follow-up in a larger number of patients are needed to confirm the efficacy and durability of the technique.